1999
DOI: 10.1021/bc9801070
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Transfer by Histidylated Polylysine/pDNA Complexes

Abstract: Plasmid/polylysine complexes, which are used to transfect mammalian cells, increase the uptake of DNA, but plasmid molecules are sequestered into vesicles where they cannot escape to reach the nuclear machinery. However, the transfection efficiency increases when membrane-disrupting reagents such as chloroquine or fusogenic peptides, are used to disrupt endosomal membranes and to favor the delivery of plasmid into the cytosol. We designed a cationic polymer that forms complexes with a plasmid DNA (pDNA) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
394
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(411 citation statements)
references
References 25 publications
13
394
3
1
Order By: Relevance
“…154 Polylysines partially substituted with histidyl residues transfect cells in the absence of endosome disrupting agents, and through a mechanism inhibited by bafilomycin A1. 155 Amphipathic cationic polymers containing strategically placed histidine residues disrupt bacterial and mammalian cell membranes in response to acidic pH, and promoted gene transfer to several cell lines at levels comparable to 25-kDa PEI. 156 The transfection efficiency of histidine-rich peptides depends on the number and positioning of histidine residues.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…154 Polylysines partially substituted with histidyl residues transfect cells in the absence of endosome disrupting agents, and through a mechanism inhibited by bafilomycin A1. 155 Amphipathic cationic polymers containing strategically placed histidine residues disrupt bacterial and mammalian cell membranes in response to acidic pH, and promoted gene transfer to several cell lines at levels comparable to 25-kDa PEI. 156 The transfection efficiency of histidine-rich peptides depends on the number and positioning of histidine residues.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…In the absence of liposomes, we found that the low molecular weight H-K polymer was not an effective transfection carrier of PCI-Luc. Although large molecular weight histidylated poly-l-lysine polymers as transfection carriers were recently demonstrated to be more effective than poly-l-lysine as carriers, 31 these histidylated polymers enhanced transfection efficiency significantly less than polyethylenimine in most cells lines. In contrast, we found that the transfection efficiency of the H-K:liposome:PCI-luc triplex was at least 10-fold greater than polyethylenimine in the absence or presence of serum (data not shown).…”
Section: Figure 6 Increased In Vivo Gene Expression With the H-k Polymentioning
confidence: 99%
“…Preparation and transfection conditions of PEI were done as previously described. 31 Duplicates were done for each concentration and each experiment was performed twice.…”
Section: ) H-s (19 Mer)-s-h-s-h-s-h-s-h-s-g-s-h-s-h-s-h-s-h-s]; and (mentioning
confidence: 99%
“…9 Lysines were expected to promote DNA condensation, conferring positive charge to the peptides, while histidines might favor the endosomal escape of DNA by the abovementioned process. 8 Various numbers of lysine and histidine residues were included in the original peptide sequence, either by replacement of a neutral amino acid or by the addition of a new residue to the sequence. The transfection efficiency showed the dependence on the number of histidine residues and on their position in the sequence, as well as on the pH at which the peptides change from an in-plane to a transmembrane alignment, the most efficient peptides being those containing 4 to 5 histidines located in the polar face of the α− helix structure.…”
Section: ■ Introductionmentioning
confidence: 99%